2005
DOI: 10.2337/diacare.28.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Vascular Inflammation in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Chronic vascular inflammation may play a role in the development of macrovascular complications in diabetic patients. In this study, we examine the association of endothelial expression of two inflammatory mediators, receptor for advanced glycation end product (RAGE) and monocyte chemoattractant protein-1 (MCP-1), with type 2 diabetes using novel endothelial biopsy and RT-PCR techniques.RESEARCH DESIGN AND METHODS -Endothelial samples are obtained from the aorta of 12 patients with type 2 diabetes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 25 publications
1
66
0
2
Order By: Relevance
“…One of the key proinflammatory mediators whose expression is stimulated by AGE and/or high glucose signaling pathway is MCP-1 [14]. Several investigators have reported that plasma levels of MCP-1 were associated with cardiovascular risk factors and may be an important biomarker during the preclinical phase of atherosclerosis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…One of the key proinflammatory mediators whose expression is stimulated by AGE and/or high glucose signaling pathway is MCP-1 [14]. Several investigators have reported that plasma levels of MCP-1 were associated with cardiovascular risk factors and may be an important biomarker during the preclinical phase of atherosclerosis [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble RAGE (sRAGE), the extracellular two thirds of the receptor, binds AGEs and interferes with their ability to bind and activate cellular RAGE. 15 We administered sRAGE (a gift from Dr Ann Marie Schmidt; 80 g IP per mouse per day) to m Lepr db and Lepr db mice for 10 days to determine whether RAGE affects the expression of TNF-␣.…”
Section: Treatment With Tnf Neutralization or Soluble Ragementioning
confidence: 99%
“…Molecules associated with the recruitment of leukocytes into the atherosclerotic plaque, such as chemoattractant cytokines and cellular adhesion molecules, are abundant in vascular lesions and seem to mediate ongoing inflammation (14,37,39). Chronic vascular inflammation is associated with oxidative stress and has been implicated in the development of diabetic vascular complications (12,25). ANG II acts as a central mediator of the oxidative and inflammatory responses in vascular disease and has been shown to induce expression of adhesion molecules and cytokines in the vasculature (7,52).…”
mentioning
confidence: 99%